Examining emergency department inequities between Māori and non-Māori: do they exist?. (30th September 2020) - Curtis, E; Paine, S; Jiang, Y; Jones, P; Raumati, I; Tomash, I; Healey, O; Reid, P
Abstract: Despite Māori (Indigenous population of New Zealand, NZ) having high Emergency Department (ED) use, few studies have explored for ethnic inequities in ED within NZ. ED healthcare can be time-pressured, complex and demanding. Clinical decision-making in this context may facilitate provider prejudice, stereotyping and bias. The Examining Emergency Department Inequities (EEDI) is a retrospective observational study, designed from a Kaupapa Māori Research position, examining ED admissions in NZ between 2006 and 2012 using the existing Shorter Stays in Emergency Department National Research Project dataset combined with clinical information extracted from NZ's National Minimum Dataset. The key predictor variable is patient ethnicity with covariates: sex, age-group, area deprivation, mode of presentation, referral method, Australasian Triage Scale and the Multimorbidity Measure (M3 Index) for co-morbidities. Generalised linear regression models investigated the associations between pre-admission variables and the measures of ED care, and mortality. There were a total of 5, 972, 102 ED events (1, 168, 944 Māori, 4, 803, 158 non-Māori). We found an increasing proportion of ED events/year, a higher proportion of Māori ED events from younger age groups and areas of high deprivation compared to non-Māori. Māori had a higher proportion of self-referral and were triaged to be seen within a longer timeframe compared to non-Māori. After controlling for year of ED event, gender, triage category, age at presentation, NZ Deprivation decile and M3 Comorbidity score: Māori had shorter ED arrival to assessment time; shorter ED Length of Stay and less Access Block (>8 hour ED LOS before ward admission). Despite this, Māori mortality within ED or within 10 days of discharge was higher than non-Māori. These findings suggest different patterns in ED usage between Māori and non-Māori. Of concern, inequities in mortality exist despite positive indicators of ED care. Key messages: There is evidence of different patterns in emergency department use between Māori and non-Māori in New Zealand. Māori:non-Māori inequities in mortality exist despite positive indicators of emergency department care.